Strengthening Character Education Through Is-lamic Religious Education - Hibatullah, Ariq; Zahra, Raudhatul Husna Amelia (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
Human beings are noble creatures, even more noble than angels. Character education is crucial to be instilled from an early age in order to develop a character that aligns with religious teachings. This research aims to analyze and explore the role of character education in the context of Islamic religious education. The main focus is to understand how character education can strengthen Islamic values within an individual. Therefore, based on research using a qualitative method with a literature review approach, the results indicate that character education plays a significantly important role in reinforcing Islamic religious education.